The Analysis Study of Efficacy of Pediatric Emergency Care Protocol: A Comprehensive Systematic Review - Muhamad Taufan Kurniawan; Mega Rizkina; Dyah Nur Chasanah (The International Journal of Medical Science and Health Research, 2025)
Background: Pediatric emergencies require unique protocols to manage critically ill or injured children. Pediatric Emergency Care Protocols (PECPs) aim to standardize assessment, triage, and intervention processes, reducing variability and improving patient outcomes. However, adherence and efficacy vary across healthcare settings, particularly in low-resource environments. A systematic review is crucial for evaluating protocols' effectiveness and adaptability. Methods: This systematic review followed PRISMA 2020 guidelines and included only full-text, peer-reviewed articles published in English between 2015 and 2025. Editorials and review papers without a DOI were excluded to ensure source quality. Relevant studies were identified through targeted searches in ScienceDirect, PubMed, and SAGE Publications. Result: An initial search across selected databases produced more than 100 potentially relevant studies. Through a structured three-phase screening process, only eight articles satisfied the predetermined inclusion criteria for detailed examination. These selected studies were subjected to rigorous critical appraisal to assess their contribution to understanding the effectiveness of pediatric emergency care protocols. This systematic approach ensured that the final analysis was based on robust evidence aligned with the study’s objectives and capable of yielding meaningful insights into this complex area. Conclusion: The Pediatric Emergency Care Protocol is a crucial tool in pediatric emergency medicine, ensuring rapid identification and management of life-threatening conditions in children. Its comprehensive disease coverage aligns with international standards, despite challenges like training gaps and limited technology access.